Effectiveness of inhaled therapies in asthma among adults in Northern Sri Lanka, a low-income and middle-income country: a prospective observational study - Guruparan, Y.; Thiyahiny, S.N.; Gowry, S.; Shalini, S.R. (BMJ Group, 2025)
Background Inhaled corticosteroids (ICS) alone, or combined with long-acting beta2-agonist (LABA), are recommended for chronic asthma. Limited access to inhaled medications hinders effective control of asthma in low-income and middle-income countries. Objective This study aimed to compare the effectiveness of inhaled therapies in a cohort of adult patients with asthma who were receiving treatment in a tertiary hospital in Northern Sri Lanka. Methods A prospective cohort study was conducted among adult patients with asthma on either ICS alone or ICS/LABA combination for at least 3 months. Participants were followed up for 6 months, with two follow-up interviews conducted 3 months apart. The primary outcome measure was asthma control, assessed by a locally validated asthma control patient-reported outcome measure. Secondary outcome measures included the use of short-acting beta2-agonists (SABA) and the percentage of patients required nebulisations and hospitalisations. McNemar’s test was used to determine the statistical significance. A p value≤0.05 was considered significant. Results Of the 1094 participants, 827 (76%) were on ICS monotherapy and 267 (24%) were on ICS/LABA. Though there were no changes in the treatment, progressive improvement in asthma control was observed from baseline to second follow-up in both ICS (54%–72%) and ICS/LABA (76%–81%) groups. Significant improvement in asthma control (p<0.001) and SABA overuse (p<0.001) at both follow-ups and nebulisation (0.008) at the first follow-up were observed in the ICS group. Conclusion Both ICS monotherapy and ICS/LABA were effective in controlling asthma. Though control was greater with ICS/LABA, the effect of additional monitoring during the follow-up was higher and significant in ICS monotherapy. Considering the low access to ICS/ LABA, a treatment package comprising ICS plus non-pharmacological approaches could be a more realistic and cost-effective treatment strategy in the local context. ICS/ LABA could be reserved for patients who fail to respond. However, this observation needs to be confirmed by interventional studies.